“Productos y atractivos turísticos del cantón Latacunga, Parroquia La Matriz”. - Chiguano Guanotoa, Jairo Ezequiel (2024)
The objective of this research was to propose strategies for the promotion and dissemination of tourist attractions and products in the Latacunga canton, La Matriz parish. Three objectives were proposed in order to complement the updating of data on tourist products and attractions of the study site. In this way, the first objective was to update the inventory of tourist attractions through the descriptive and bibliographic method, using different techniques such as interviews with key people, through the Methodological Guide for the Hierarchization of Attractions and Generation of Tourist Spaces, which was used as an instrument for filling out forms for each attraction, allowing the attractions obtained to be categorized and prioritized to obtain a database. On the other hand, the second objective of inventorying tourist products, the Methodology for Planning Tourism Products of Peru was used, covering a study of the current situation of the territory through descriptive research and a deductive method to inventory the existing tourist products of the parish. Finally, the third objective was carried out with the SWOT Matrix tools of the tourist attractions and products of the parish, consecutively the matrices (MEFI), (MEFE) and the crossed SWOT were developed that allowed obtaining results of promotion and dissemination strategies, helping to have strategic alliances with governmental and non-governmental authorities.